Gender Differences in Adverse Drug Reactions Among Adult Patients Reported to the Iraqi Pharmacovigilance Center - Areej Atheer Alsaedi; Dheyaa j. Kadhim; Manal M. Younus (College of Pharmacy University of Baghdad, 2021)
For many years it was argued that there may be a gender differences in adverse drug reactions (ADRs). This assumption was based on many possible factors such as hormonal or behavior differences, and it was not clearly identified since the female gender was not preferred to be enrolled in many clinical trials. The primary aim of this study was to assess the extent of possibly relevant gender differences in drug-ADRs regarding causality, severity, preventability, seriousness, expectedness and outcome. While the secondary aim was to assess for which group of drugs and for which ADRs gender differences are identified most often. The study was a retrospective one that depends on processing a specially selected group of data obtained from the Iraqi Pharmacovigilance Center database. The data included consisted of 3833 individual case safety reports sent during the period from 1st January 2017 to 31st December 2019. It was found that the reported adverse drug reactions for females (60.84 %) were much more than males (39.16 %). In addition, significant differences in age group distribution of adverse drug reactions were found in which females in their reproductive age had more adverse drug reactions while the older adult males were more likely to suffer adverse drug reactions if compared with the same age groups from the opposite gender. The highest type of adverse drug reactions for both genders were those that fall in the skin and subcutaneous tissue disorders (26.4 % in females) and (22.6 % in males) with statically significant difference between the two genders. While the highest group to cause adverse drug reactions was the systemic anti-infective agents with a greater chance 'statistically significant' in females to suffer a side effect from this group of medications (40.8 %) compared to male gender (35.5 %). The frequency of serious adverse drug reactions was significantly more prevalent in females (45.4 %) than for males (41.3 %) while the fatal outcome was significantly more observed in males (0.8 %) as compared with females (0.2 %). The expectedness analysis gave the finding that for each gender the expectedness of adverse drug reactions was nearly equal.